1981
DOI: 10.2105/ajph.71.2.127
|View full text |Cite
|
Sign up to set email alerts
|

The influence of patient-practitioner agreement on outcome of care.

Abstract: A previous study suggested that patientpractitioner agreement and follow-up in ambulatory care facilitates problem resolution as judged by patients. In this study in another medical practice, practitioner-patient agreement on what problems required follow-up was associated with greater problem resolution as judged by the practitioners regardless of the severity of the problems. In this study, patients did not judge problems mentioned only by themselves to be less improved than problems mentioned by both them a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
1
13

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(160 citation statements)
references
References 15 publications
5
140
1
13
Order By: Relevance
“…[1][2][3][4] Experts have advocated for a shift in patient-physician relationships from a directive style to a more collaborative interaction. [19][20][21] This shared decision-making model elicits patient preferences and emphasizes the patient's understanding of the risks and benefits of diagnostic and therapeutic decisions, alternatives, and uncertainties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Experts have advocated for a shift in patient-physician relationships from a directive style to a more collaborative interaction. [19][20][21] This shared decision-making model elicits patient preferences and emphasizes the patient's understanding of the risks and benefits of diagnostic and therapeutic decisions, alternatives, and uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in ambulatory settings document that agreement between patients and physicians regarding the diagnosis and treatment plan is associated with improved medication adherence and better outcomes. [1][2][3][4] Hospital settings pre sent unique challenges to the patient-physician relationship, including the lack of a prior relationship, rapid pace of clinical care, and dynamic nature of inpatient medical teams. Prior studies revealed important findings about the relationship between hospitalized patients and health care professionals.…”
mentioning
confidence: 99%
“…Close the interview less critical than the perception by patients that they are the focus of the time and that they are accurately heard. Other aspects important to the relationship include eliciting patients' own explanations of their illness, 23,24 giving patients information, 25,26 and involving patients in developing a treatment plan. 27 (For an overview of this area of research, see Putnam and Lipkin, 1995.…”
Section: A Special Relationshipmentioning
confidence: 99%
“…6,7 Agreement between clinicians and patients regarding the assessment of presenting clinical symptoms is important for patient satisfaction [8][9][10][11][12] and symptom resolution. [13][14][15] In research, differences in estimations of the prevalence or incidence of symptoms that are dependent on data source can lead to substantial differences in estimated disease parameters. 16 An understanding of the relative agreement and disagreement between the occurrence of symptoms by self-report compared with medical records can be useful in the interpretation of the clinical and research literature.…”
Section: Introductionmentioning
confidence: 99%